Verification of the worst case model for the estimation of average intensity of the electromagnetic background created by base stations of cellular communications - V. I. Mordachev (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
Results of comparison estimations of average intensity of the electromagnetic background created by base stations of cellular communications, performed with use of the technique offered by the author, with the published results of measurements of levels of an electromagnetic background in the various countries, are presented. This data confirms of adequacy of the offered technique and its practical importance for an estimation of electromagnetic ecology of different areas and electromagnetic safety of the population.